Clinical and Functional Characterization of a Novel Mutation in AVPR2 Causing Nephrogenic Diabetes Insipidus in a Four-Generation Chinese Family - Guo, Shusen; Wu, Shimin; Li, Zhuxi; Huang, Lianjing; Zhan, Di; Zhang, Cai; Luo, Xiaoping (Frontiers in Pediatrics, 2021)
Background: Congenital nephrogenic diabetes insipidus (CNDI) is a rare inherited disease that is caused by mutations in arginine vasopressin receptor 2 (AVPR2) or aquaporin 2 (AQP2). Functional analysis of the mutated receptor is necessary to verify the impact of the mutation on receptor function and suggest some possible therapeutic strategies for specific functional defects. Methods: Family history and clinical information were collected. Whole-exome sequencing and sanger sequencing were performed to determine the potential genetic cause of diabetes insipidus. The identified variant was classified according to the American College of Medical Genetics (ACMG) criteria. Bioinformatic analysis was performed to predict the function of the identified variation. Moreover, wild-type and mutated AVPR2 vectors were constructed and transfection to HEK-293T cells. Immunofluorescence experiments were performed to investigate the expression and localization of the mutated protein and cAMP parameter assays were used to measure its activity in response to AVP. Results: The heights of the adult members affected with polyuria and polydipsia were normal, but all affected children had growth retardation. Next-generation sequencing identified a novel mutation in AVPR2 gene (c.530T > A) in this family. Bioinformatic analysis indicated that the mutation in AVPR2 changed the hydropathic characteristic of the protein and was probably deleterious. Although immunofluorescence showed that the mutated AVPR2 was normally expressed in the cell surface, the intracellular cAMP concentration stimulated by AVP was significantly lower in cells transfected with mutated AVPR2 than cells transfected with wild-type AVPR2. Based on the ACMG criteria, the novel c.530T > A variant of the AVPR2 gene was likely pathogenic and the affected family members were diagnosed as CNDI. After the confirmation of the diagnosis, the proband was treated with compound amiloride hydrochloride and rhGH, the symptoms of polyuria, polydipsia and growth retardation were all improved. Conclusion: These findings suggested that the novel mutation in AVPR2 (c.530T > A) was a true disease-causing variant with mild effects, which could be classified as a type III mutant receptor. Moreover, investigations of the function of growth hormone axis could be important for the pediatric CNDI patients with extreme short stature, and rhGH treatment might improve the final adult heights in these patients.